Dominica : 2018 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2018)
This 2018 Article IV Consultation highlights that in 2018, Dominica's output is projected to decline by 14 percent and to take about 5 years to recover to pre-hurricane levels. The fall in output and government revenue, coupled with increased expenditure for rehabilitation and reconstruction, will lead to a substantial worsening of fiscal and external deficits. However, signs of recovery, particularly in construction and the public sector, have already started to emerge. The risks to the outlook include the budget becoming financially constrained and unable to sustain adequate investment given high debt, limited buffers, weak revenue, and urgent needs for reconstruction spending. Other risks include financial instability stemming from undercapitalization of systemic financial institutions, recurrent natural disasters, and external competitiveness challenges.